Monte Carlo simulations of Cu/Ni–Si–Mn co-precipitation in duplex stainless steels. (1st August 2020) - Frazier, William E.; Lach, Timothy G.; Byun, Thak Sang
Abstract: First-Passage Kinetic Monte Carlo (FPKMC) simulations of species migration in duplex stainless steels were performed in order to establish relationships between alloy content, segregation behavior, and the formation of Ni–Si–Mn rich particles in cast duplex stainless steels during thermal aging. The Ni–Si–Mn-rich second phase forms after extended aging at reactor operating temperatures and degrades alloy properties. Simulations of Ni–Si–Mn cluster formation were validated through comparison with experimental results obtained through Atom Probe Tomography (APT) on similar alloy compositions, identifying several trends. First, Cu promotes the formation of Ni–Si–Mn clusters, but only when Ni or Mn prefer segregation to the surface of Cu particles; without the segregation of these species, the critical composition for the clusters to form was not achieved. Second, the width of precipitate-denuded zones near γ/δ interfaces increases with decreasing Cu content. This finding was in strong agreement with APT and Scanning Transmission Electron Microscopy results, further validating our model. Finally, our model predicts that Ni–Si–Mn cluster formation will be the most extensive when the Si:Mn ratio is approximately 1:1 and the least extensive when one of these key elements is less concentrated (Mn ≤ 0.5 at.% or Si ≤ 0.5 at.%). The implications of these results on how to improve alloy properties are discussed. Graphical abstract: Image, graphical abstract